PENGARUH MORALITAS INDIVIDU, RELIGIUSITAS DAN BYSTANDER EFFECT TERHADAP KECENDERUNGAN KECURANGAN AKUNTANSI (FRAUD) - I Made Restu Gunayasa; Ni Wayan Alit Erlinawati (Hita Akuntansi dan Keuangan, 2020)
Fraud (fraud) is an error that is carried out in a deliberate manner, within the scope ofaccounting, the concept of fraud (fraud) is a deviation from an accounting procedure that shouldbe applied in an entity. The purpose of this research is to find out the effect of individual morality,religiosity and bystandery effecti on the tendency of accounting (fraud) tendencies in LPD inKecamatan Marga. This research was carried out throughout the LPD office located inKecamatan Marga appreciate, with as many as 46 samples. The sample determination methodused is non-probability sampling, namely by means of purposive sampling, while the data analysistechnique used is multiple linear regression analysis. The results of the study show that: (1)Individual moralization has a negative influence on the tendency of accounting fraud (fraud), (2)Religiosity has a negative influence on accounting tendency (fraud), (3) System effect has apositive influence on accounting tendency (fraud).